Host control by SPβ phage regulatory switch as potential manipulation strategy. (February 2023) - Floccari, Valentina A; Dragoš, Anna
Abstract : The interaction between temperate phages and their bacterial hosts has always been one of the most controversial in nature. As genetic parasites, phages need their hosts to propagate, while the host may take advantage of the genetic arsenal carried in the phage genome. This intriguing host–parasite interplay with an evident mutualistic implication could be challenged by recent discoveries of alternative phage lifestyles and regulatory systems that seem to support a manipulative strategy pursued by the phage. Through two fascinating novel mechanisms concerning the active lysogeny and a phage-encoded quorum sensing system, referred as 'Arbitrium', employed by SPβ-like phages of Bacilli, we propose the parasite manipulation as ecological relationship between certain temperate phages and bacteria. Highlights: Temperate phage may alter host phenotype during lysogeny with benefits for the host. Gene switching via active lysogeny may harm the host and promote phage transmission. By Arbitrium system phage converts the host to secrete signals for its own benefit. Lysogenic conversion by some phages could stand for parasite-adaptive manipulation.